STRATEGI SALES PROMOTION DALAM MENINGKATKAN PENJUALAN INDIHOME DENGAN PENDEKATAN STOP-SIT: (Studi Kasus IndiHome Cikarang Barat PT. Telkom Indonesia) - Kirana, Rahmania Mega; Setianingrum, Vinda Maya (The Commercium, 2024)
This research aims to discover the sales promotion strategies implemented by IndiHome Cikarang Barat using the STOP-SIT approach. The STOP-SIT approach is applied comprehensively, encompassing market segmentation, targeting, objectives, positioning, tool selection, integration of online and offline strategies, and continuous monitoring and evaluation. The results indicate that there are three main segments targeted by IndiHome Cikarang Barat: students and productive workers (17-40 years old) as the primary target, business owners (30-50 years old) as the secondary target, and homeowners (40-60 years old) as the tertiary target. IndiHome Cikarang Barat positions itself as a superior solution by offering reliable connectivity, extensive network coverage, and flexible service package options, addressing the dissatisfaction of the community with local WiFi services. Online strategies include the IndiHome Virtual Run and Ride, e-sports competitions, collaborations with online streaming platforms, bundling promotions, and content marketing. Offline strategies include participation in local events, booth openings, the role of WiFi.ID Corner, and open table activities.